Children Born of Rebel Captivity: Politics and Practices of Integration in Uganda - Kiconco, Allen (Frontiers in Political Science, 2022)
Many studies have documented and analyzed the Lord's Resistance Army (LRA) forced conjugal association patterns and practices (“forced marriage”). However, the focus has been on the experiences of abducted girls forced to serve as conjugal partners to commanders (“forced wives”). The experiences of children born as a result of these relationships are under-investigated. Receptor communities in northern Uganda are assumed to be places of hope, comfort, and protection for these children. However, they can also be hostile, leaving the children in precarious and vulnerable situations. This article draws from ethnographic fieldwork in the Acholi region and interviews with formerly abducted mothers focusing on their children's integration processes and experiences. It argues that return is not integration, as it often coincides with further exclusion and alienation. In Uganda's patriarchal and patrilineal social systems, children with no paternal lineage are viewed as of lower status. Stigmatization facing children born of the LRA captivity condemns them to this status, consequently excluding them from mainstream society. Findings show that stigma remains central to the life experiences of these children several years after the end of the conflict in 2006. Their persistent stigmatization is linked to broader discriminatory socio-cultural and patriarchal ideas and practices.